2009
DOI: 10.1021/la9005955
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Elastic Strains on the Adsorption Process in Porous Materials: An Experimental Approach

Abstract: The experimental results presented in this paper show the influence of the elastic deformation of porous solids on the adsorption process. With p + -type porous silicon formed on highly boron doped (100) Si single crystal, we can make identical porous layers, either supported by or detached from the substrate. The pores are perpendicular to the substrate. The adsorption isotherms corresponding to these two layers are distinct. In the region preceding capillary condensation, the adsorbed amount is lower for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 36 publications
2
40
0
Order By: Relevance
“…We have found that methane and methanol adsorption can induce both pore shrinkage and expansion. The solvation pressure exerted by the adsorbate is a major reason for changes in pore dimension [12,13]. Solvation pressure itself can vary strongly with pore width, the nature of the adsorbate, and with adsorbate density and thus with temperature ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have found that methane and methanol adsorption can induce both pore shrinkage and expansion. The solvation pressure exerted by the adsorbate is a major reason for changes in pore dimension [12,13]. Solvation pressure itself can vary strongly with pore width, the nature of the adsorbate, and with adsorbate density and thus with temperature ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…More recent experimental work on the deformation of carbons during the adsorption of different gases has been reported by Fomkin and co-workers [6][7][8] and a dilatometric investigation of the deformation of carbon xerogels has been made by Balzer and co-workers [9] who concluded that micropores in the adsorbents made the most significant contribution to the expansion and contraction of these materials. Recognizing the significance of the effect of adsorption-induced deformation, more attention is paid on this phenomenon for various systems beside carbonaceous materials, such as porous glass [10], zeolites [11], silica gels [12], porous silicon [13,14] and metal-organic frameworks (MOFs) [15,16]. A review of the general area of adsorption deformation has been published by Tvardovski [17].…”
Section: Introductionmentioning
confidence: 99%
“…2 This seems unlikely to us given that nitrogen is a wetting liquid for most surfaces due to the dominant contribution from dispersion forces and heterogeneity would typically enhance wetting in this case. It has also been suggested that the hysteresis in all these Psi systems can be explained by flexibility of the materials [8][9][10][11][12] but measurements of the effect of capillary condensation on the volume of Psi suggest a rather weak effect. 13 Understanding of this phenomenon may require comprehensive studies of not only thermodynamics, but also dynamics of fluids confined to disordered porous materials.…”
Section: Introductionmentioning
confidence: 99%
“…It is traditional to get macroscopic hysteresis from the working of an assembly of microscopic hysteretic elements [18]. However, as is known in a different context [6], suspected in the current context [19], and as the models we have introduced show, there is another route to hysteresis. There are circumstances in which systems evolve among mesoscopic structures that are not easily reached from one another.…”
Section: Discussionmentioning
confidence: 98%